Responsabilização Pós-Consumo e Logística Reversa:: O Caso das Embalagens de Agrotóxicos no Brasil (Sustainability in Debate, 2010)
The pesticides packages bring risk of human and environmentalcontamination. This paper presents an analysis from the perspective ofsustainability, system of collection and disposal of pesticides packagesin Brazil, created from the Law 9974/2000, which established liabilityfor after consumption packaging. In 2002 was created the NationalInstitute of Packaging Processing (Inpev) that uses the principle ofReverse Logistics, aiming to return the packages to the business cycleby recycling. It was found that the system has contributed to thereduction of environmental impacts and requires amendments tosustainability.